Cardiovascular Disease Burden: Evolving Knowledge of Risk Factors in Myocardial Infarction and Stroke through Population-Based Research and Perspectives in Global Prevention - Oliveira, Gustavo B. F.; Avezum, Alvaro; Roever, Leonardo (Frontiers in Cardiovascular Medicine, 2015)
Current knowledge and research perspectives on the top ranking causes of mortality worldwide, i.e., ischemic heart disease and cerebrovascular diseases have developed rapidly. In fact, until recently, it was considered that only half of the myocardial infarctions were due to traditional risk factors such as hypertension, hypercholesterolemia, smoking and diabetes. In addition, most of the available evidence of incidence, risk factors, and clinical outcomes, if not all of it, was derived from studies conducted in developed countries, which included lower proportion of female individuals and with low ethnic diversity. Recent reports by the WHO have provided striking public health information, i.e., the global burden of cardiovascular mortality for the next decades is expected to predominantly occur among developing countries. Therefore, multi-ethnic population-based research including prospective cohorts and, when appropriate, case-control studies, is warranted. These studies should be specifically designed to ascertain key public health measures such as geographic variations in noncommunicable diseases, diagnosis of traditional and potential newly discovered risk factors, causes of death and disability, and gaps for improvement in healthcare prevention (both primary and secondary) and specific treatments. As an example, a multinational, multiethnic population-based cohort study is the Prospective Urban and Rural Epidemiology (PURE) study, which is the largest global initiative of 150,000 adults aged 35-70 yrs, looking at environmental, societal and biological influences on obesity and chronic health conditions such as ischemic heart disease, stroke and cancer among urban and rural communities in low-, middle-, and high-income countries, with national, community, household and individual-level data. Implementation of population-based strategies is crucial to optimizing limited health system resources while improving care and cardiovascular morbidity and mortality.